Synthesis of superhard nanodispersed titanium compounds in a magnetoplasma accelerator operating in pulse-periodic regime; Russian Physics Journal; Vol. 54, iss. 10 - Sivkov A. A. Aleksander Anatolyevich; Gerasimov D. Yu. Dmitry Yurievich; Saigash A. S. Anastasiya Sergeevna; Evdokimov A. A. Andrey Anatolievich (2012, 2012)
Title screen